Arbitrary distance and angle measurement by dynamic dispersive interferometry using a frequency comb. (October 2021) - Xu, Xinyang; Zhao, Haihan; Bi, Ying; Qian, Zhiwen; Liu, Chao; Shi, Haonan; Zhai, Jingsheng
Highlights: This paper presents a distance and angle measurement method combining dynamic comb spacing and optical delay lines. Arbitrary distance and angle measurement can be achieved while maintaining high accuracy. Dispersive interferometry employing the dynamic scheme extremely extends the measurable range of distance and angle. This method inspires the commercial value of the frequency combs and fits into industrial manufacturing scenarios. Abstract: Arbitrary distance and angle measurement play an important role in the intelligent industry, where accuracy and measurable range are critical for determining the object position in large-scale manufacturing scenarios. Using the dynamic comb spacing with long delay lines, we experimentally demonstrate dynamic dispersive interferometry, which performs high-accuracy measurement for arbitrary distances and angles. By the benefit of the dynamic scheme, the dispersive interferometry gets rid of the limitation of spectrometer resolution. Consequently, the method is given a great measurable range for the distances and angles. To verify the performance of the presented method, we devise experiments for the two above geometric quantities respectively. The results prove the differences can be well within 2.3 μm at 21 m range, and 2.9 arcsec at ±40° compared to reference values.